2018
DOI: 10.1371/journal.pone.0190014
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of two silicate-based materials, Biodentine and BioRoot RCS, on dental pulp stem cells in models of reactionary and reparative dentinogenesis

Abstract: BackgroundCalcium silicate-based cements are biomaterials with calcium oxide and carbonate filler additives. Their properties are close to those of dentin, making them useful in restorative dentistry and endodontics. The aim of this study was to evaluate the in vitro biological effects of two such calcium silicate cements, Biodentine (BD) and Bioroot (BR), on dental stem cells in both direct and indirect contact models. The two models used aimed to mimic reparative dentin formation (direct contact) and reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
34
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 24 publications
(33 reference statements)
7
34
0
10
Order By: Relevance
“…Interestingly, in the case of PGE2 concentration in macrophages incubated with Biodentine TM for 48 h, we found a statistically insignificant lower concentration of this prostaglandin in relation to control. These findings confirm the suggestions of the anti-inflammatory properties of silicate base material [36]. Our results also indirectly confirm the observations of Loison-Robert et al (2018), [36] whose in vitro studies conducted on human cells and dental stamina cells, incubated as in our model directly from Biodentine TM, showed a lack of inflammation induction.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Interestingly, in the case of PGE2 concentration in macrophages incubated with Biodentine TM for 48 h, we found a statistically insignificant lower concentration of this prostaglandin in relation to control. These findings confirm the suggestions of the anti-inflammatory properties of silicate base material [36]. Our results also indirectly confirm the observations of Loison-Robert et al (2018), [36] whose in vitro studies conducted on human cells and dental stamina cells, incubated as in our model directly from Biodentine TM, showed a lack of inflammation induction.…”
Section: Discussionsupporting
confidence: 93%
“…These findings confirm the suggestions of the anti-inflammatory properties of silicate base material [36]. Our results also indirectly confirm the observations of Loison-Robert et al (2018), [36] whose in vitro studies conducted on human cells and dental stamina cells, incubated as in our model directly from Biodentine TM, showed a lack of inflammation induction. They also showed that the incubation of Biodentine cells showed no significant cytotoxicity but some cells showed apoptosis in direct contact.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Biodentine (Septodont, Saint-Maur-des-Fossés, France) is composed mostly of tricalcium silicate, zirconium oxide, and calcium carbonate powder, which are mixed with a supplied solution that includes calcium chloride [12,13]. The reduced setting time compared to MTA is achieved by diminishing the particle size and adding calcium chloride to expedite the reactions [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The substitution of bismuth oxide with zirconium oxide may also play a role in reduced setting time, because this component has been reported to expedite the primary hydration reaction [13]. Previous studies of this material's effects on dental pulp stem cells demonstrated its biocompatible ability, odontoblast differentiation ability, and mineralization potential [12,16]. Endocem Zr (Maruchi, Wonju, Korea) and RetroMTA (BioMTA, Seoul, Korea) were developed to cause less tooth discoloration compared to ProRoot MTA [17].…”
Section: Introductionmentioning
confidence: 99%